Pemanfaatan Teknologi Informasi Dan Komunikasi (TIK) Dalam Meningkatan Mutu Perguruan Tinggi Agama Hindu - I Gede Agus Krisna Warmayana (Jurnal Penjaminan Mutu, 2018)
Information and Communication Technology (ICT) is a fundamental requirenment in Education. ICT plays an important role in improving the quality of higher education. In improving the quality of higher education, especially Hindus-based colleges, a management model of academic service management is needed in terms of policy makers, planners, organizers, implementers, and controlling the quality of academic services. The data was collected throughout observation, interviews, and document analysis. Particularly for data analysis, an interactive model was used including data collection, data reduction, data display, and conclusions. The results of this study indicated that the application of quality management of ICT-based academic services is highly effective in higher education because of policy documents and quality control instrumentation which resulted on an optimal and fast service processes, easy coordination and integration between many ICT-based academic service institutions, academic information system database (SIAKAD) and PDDIKTI, a qualified control institutions specifically in aspects of institutional structure, human resources, and quality instrumentation; and there is a commitment from all steakholder owners to implement a quality and ICT-based culture.